The Innovator's Playbook : how to design great products, services and experiences your customers will love - Baird, Nathan (John Wiley and Sons Australia, Ltd, 2020)
Take a Design-led Approach to Innovation Innovation drives growth in organisations and entire economies. Yet innovation is hard, risky and rarely successful. Most innovations and startups fail because of a lack of focus on the front end of the innovation process where customer needs are researched, insights are distilled, solutions are ideated, prototyped and tested and business models are shaped. But innovation doesn't have to be this way. In'Innovator's Playbook, author and leading Design Thinking expert Nathan Baird shares his 20 years of hands-on experience, tools and methods for developing a winning customer-centric approach to innovation. This book will teach you how to apply the design thinking method to innovation and help you to innovate better with five practical and proven stages: 1. Build the right team for innovation. 2. Better understand your customer through empathy. 3. Distill and refine customer-centric needs and insights. 4. Unleash your team's creativity to create fresh new ideas to address customer needs. 5. Experiment and validate desirable, feasible and viable solutions. Innovator's Playbook helps entrepreneurs, corporate teams, startups and leaders across all levels to use design-led methodologies for start-to-finish innovation success.